Analisis Misalignment Pada Unit High Pressure Fluidized Bad Menggunakan Dial Indicator - Suherna, Suherna; Kelana, Nikho Bayu Kusuma; Nurdin, Akhmad (IDENTIFIKASI, 2022)
Rotation machines are one of the driving machines that are widely used in industrial factories because they are strong, reliable, easy to maintain and efficient. Installation of the machine with other equipment requires accuracy so that the axis between the two is truly an axis of "alignment". The importance of accurate alignment of the machine is the main reason for conducting this research, repairs that occur in the machine that require a shift between the motor and fan from their initial position need to be aligned. The method used is a rim and face dial indicator, measuring the axle on the face and rim hub that does not move and measuring the soft foot that occurs on the motor and aerator legs and measuring run out of the clutch at positions 0°, 90°, 180° and 270°. After getting the results of pre-alignment measurements and calculations, the HPFB A position of the aerator must be added with a shim for IB of 1,4 mm and OB of 1,99 mm. To shift the aerator the IB leg needs to be shifted to the left by 0,5 mm and the OB leg is shifted to the right by 1,1 mm. HPFB B aerator position must be added by shim for IB of 1,26 mm and OB of 1,86 mm. To shift the aerator, the IB leg needs to be shifted to the left by 0,45 mm and the OB leg is shifted to the right by 0,96 mm. HPFB C aerator position must be added with shim for IB of 1,4 mm and OB of 1,99 mm. To shift the aerator, the IB foot needs to be shifted to the left by 0,6 mm and the OB leg is shifted to the right by 1 mm.